Membangun Kesatuan Gereja di Tengah Keberagaman Budaya di Indonesia - Suang Manik (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The Republic of Indonesia is well known as a country with abundant cultural and ethnic diversity, in this case it will also be at once a challenge and an opportunity for church unity. On the one hand, this diversity can be a spiritual richness that enriches church communities, but on the other hand, potential differences can also be a hindrance to unity. This article focuses on efforts to build church unity in the context of cultural diversity in Indonesia. The article will also argue that cultural diversity is not an obstacle, but rather an opportunity to enrich the witness of faith through a united church in the midst of various differences.